THE REFLECTION OF STUDENTS EFL CLASSROOMS ANXIETY IN UNDERGRADUATE PROGRAM - Nirwana, Gusti Puspita; Rosayanti, Novinda; Mahrus, Miftahul (Premise: Journal of English Education and Applied Linguistics, 2023)
Anxiety is one of the constraints affecting EFL learners in acquiring the target language of the communicative classroom contexts, especially for university students. Therefore, the research aims to shed light on the students' English foreign language classroom anxiety in undergraduate programs. The research employed a qualitative approach with a case study design. This research involved sixty-two students in an undergraduate program. Purposive sampling was applied in this research to select the participants. The instruments used in this study were questionnaires and semi-structured interviews. The Questionnaire adopted from Horwitz, Horwitz, and Cope (1986) consisted of 33 items. The result revealed that the average student's anxiety level was 114, categorized as anxious in the EFL classrooms. Another result showed that the students experienced some symptoms and phenomena based on the three subdimensions, indicating anxiety in EFL classrooms.